Typification and notes on fruit colour of Viscum orientale (Santalaceae) - Naskar, Saikat; Bhadra, Ruma (Phytotaxa, 2017)
The name Viscum orientale is here lectotypified. For precise application of the name, an epitype is also designated. Fruit colour of the species as stated in the protologue differs from our observation from Indian Sundarban. The probable reasons for incorrect information in the protologue have been clarified.